2006
DOI: 10.1016/j.applanim.2005.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory behaviour and stereotypical behaviour in farmed mink (Mustela vison) in the presence, absence and after the removal of swimming water

Abstract: Captive animals are often provided with cage enrichments in order to improve their welfare. Swimming water is an often-discussed requirement for farmed mink. The present study aimed to give insight into the value of swimming water for farmed mink by measuring anticipatory and stereotypical behaviour in subjects raised and housed in the presence and absence of swimming water and in subjects that were deprived of swimming water.The major findings of the present experiments are that: (1) there was no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In the literature, wanting is described to be related to an enhanced sensitivity to reward (Berridge, 1996;Berridge and Robinson, 1998). This enhanced sensitivity of the reward system in the absence of a water bath was not demonstrated in the study of Vinke et al (2006). However, other studies showed that a subsequent blockade appeared frustrating for mink that had previous contact with swimming water (Mason et al, 2001;Korhonen et al, 2003;Mohaibes et al, 2002Mohaibes et al, , 2003Vinke, 2004).…”
Section: Some Specific Points Of Discussion On the Results In The Avamentioning
confidence: 97%
See 3 more Smart Citations
“…In the literature, wanting is described to be related to an enhanced sensitivity to reward (Berridge, 1996;Berridge and Robinson, 1998). This enhanced sensitivity of the reward system in the absence of a water bath was not demonstrated in the study of Vinke et al (2006). However, other studies showed that a subsequent blockade appeared frustrating for mink that had previous contact with swimming water (Mason et al, 2001;Korhonen et al, 2003;Mohaibes et al, 2002Mohaibes et al, , 2003Vinke, 2004).…”
Section: Some Specific Points Of Discussion On the Results In The Avamentioning
confidence: 97%
“…Some studies reported that mink subjects were performing stereotypical patterns inside or in the presence of a water bath (Skovgaard et al, 1997a;Mohaibes et al, 2002Mohaibes et al, , 2003Vinke, 2004). Vinke et al (2006) found no differences in anticipatory or in stereotypical behaviour in 4 months respectively 10 months old mink, in the presence and absence of swimming water (N= 56 females in total; Water present vs absent: 24 subjects per group). Mohaibes et al (2002Mohaibes et al ( , 2003 investigated the effects of a swimming bath on stereotypical behaviour: they found that mink with baths had less frequent stereotypic behaviour than mink without baths.…”
Section: Stereotypies In the Presence And Absence Of A Water Bathmentioning
confidence: 99%
See 2 more Smart Citations
“…First, unlike ARL, it often appears to be directed at other mink, and other authors have reported that similar "scratching" seems to be an attempt to enter an area to which access is denied [55]. Second, some authors consider such behaviour to be an ARB if it is repetitive enough [56], while others never do [57].…”
Section: Introductionmentioning
confidence: 99%